2022
DOI: 10.4103/njcp.njcp_1894_21
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Vitamin D Receptor Gene Polymorphisms and Periodontitis in Turkish Individuals with Type 2 Diabetes Mellitus

Abstract: Background and Aim: Vitamin D receptor (VDR) gene polymorphisms have been implicated in the pathogenesis of many diseases, such as periodontitis and diabetes mellitus (DM). The present study aimed to evaluate the distributions of VDR polymorphisms in diabetic individuals with healthy periodontium (DMH), diabetic individuals with periodontitis (DMP), nondiabetic individuals with healthy periodontium (H), and nondiabetic individuals with periodontitis (P). Material a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Also, other studies conducted on Pakistani [37] and Jordanian [38] individuals demonstrate the potential relationship of this VDR polymorphism with susceptibility to T2D. Another published paper indicates that individuals with T2D and the C allele of rs2228570 may have an increased risk of periodontitis [28]. In contrast, some investigations show no significant association between rs2228570 and T2D [23,29] or glycemic status [23,39].…”
Section: Recent Findingsmentioning
confidence: 98%
See 1 more Smart Citation
“…Also, other studies conducted on Pakistani [37] and Jordanian [38] individuals demonstrate the potential relationship of this VDR polymorphism with susceptibility to T2D. Another published paper indicates that individuals with T2D and the C allele of rs2228570 may have an increased risk of periodontitis [28]. In contrast, some investigations show no significant association between rs2228570 and T2D [23,29] or glycemic status [23,39].…”
Section: Recent Findingsmentioning
confidence: 98%
“…A study by Liu et al indicates that it may be associated with a reduced risk of T2D in Asians [12 ▪▪ ]. Another study indicates that the G allele of the rs1544410 may be associated with T2D in individuals with healthy periodontium [28]. Maulood et al found a significantly higher fasting blood glucose value in patients with rs1544410 G/A and A/A genotypes and a higher triglyceride value in diabetic patients with the G/A genotype.…”
Section: Recent Findingsmentioning
confidence: 99%